2023
DOI: 10.1371/journal.pone.0288134
|View full text |Cite
|
Sign up to set email alerts
|

RT-DOb, a switch gene for the gene pair {Csf1r, Milr1}, can influence the onset of Alzheimer’s disease by regulating communication between mast cell and microglia

Abstract: In biology, homeostasis is a central cellular phenomenon that plays a crucial role in survival. The central nervous system (CNS) is controlled by exquisitely sensitive homeostatic mechanisms when facing inflammatory or pathological insults. Mast cells and microglia play a crucial role in CNS homeostasis by eliminating damaged or unnecessary neurons and synapses. Therefore, decoding molecular circuits that regulate CNS homeostasis may lead to more effective therapeutic strategies that specifically target partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the area under the receiver operating characteristic (ROC) curve (AUC) is widely employed to evaluate the performance of supervised classification models 20 . In our analysis, we utilized ROC curves to assess the sensitivity and specificity of the Random Forest model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the area under the receiver operating characteristic (ROC) curve (AUC) is widely employed to evaluate the performance of supervised classification models 20 . In our analysis, we utilized ROC curves to assess the sensitivity and specificity of the Random Forest model.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of RT-DOb /{ Csf1r , Milr1 } triplet in onset of Alzheimer’s disease has been suggested and validated in previous studies. These studies indicated the change in expression level of RT-DOb gene, as a switch gene, can disturb the communication between mast cell and microglia 19 , 20 . Another study suggested the Rps27a gene can act as a switch gene for { Il-18 , Cx3cl1 } gene pair and be associated with pathogenesis of the major neurodegenerative diseases by controlling the microglia activation 21 .…”
Section: Introductionmentioning
confidence: 99%